Evaluative and Experienced Well-being of Caregivers of Parents and Caregivers of Children. (2nd June 2016) - Hammersmith, Anna M; Lin, I-Fen
Abstract: Objectives: Informal caregiving is an important source of support for aging parents and children. Yet the timing and nature of caring for parents versus children may result in different levels of well-being. Despite extensive studies on the well-being of caregivers of parents and of children, it remains elusive as to how evaluative and experienced well-being vary by caregiver type. Method: Using data from the 2012 and 2013 rounds of the American Time Use Survey, we examined how 216 caregivers of parents and 1, 989 caregivers of children reported their evaluative well-being (life satisfaction) and experienced well-being (happiness, meaning, pain, sadness, stress, and tiredness). Results: Caregivers of parents reported lower evaluative and experienced well-being than caregivers of children. The association between caregiver type and life satisfaction dissipated, whereas the associations of caregiver type with happiness, meaning, and sadness persisted after accounting for caregivers' demographic characteristics, socioeconomic resources, and time intensity. Discussion: Experienced well-being appears to be more sensitive than evaluative well-being in detecting differences in well-being between these two types of caregivers. Given that the caregivers of parents do not receive the same level of institutional support as caregivers of children, social policies should aim to provide caregivers of parents with additional support.